Ethnic Disparities in Hospitalization for COVID-19: a Community-Based Cohort Study in the UK - Lassale, Camille (medRxiv, 2020)
IMPORTANCE: Differentials in COVID-19 incidence, hospitalization and mortality according to ethnicity are being reported but their origin is uncertain. OBJECTIVE: We aimed to explain any ethnic differentials in COVID-19 hospitalization based on socioeconomic, lifestyle, mental and physical health factors. DESIGN: Prospective cohort study with national registry linkage to hospitalisation for COVID-19. SETTING: Community-dwelling. PARTICIPANTS: 340,966 men and women (mean age 56.2 (SD=8.1) years; 54.3% women) residing in England from the UK Biobank study. EXPOSURES: Ethnicity classified as White, Black, Asian, and Others. MAIN OUTCOME(S) AND MEASURE(S): Cases of COVID-19 serious enough to warrant a hospital admission in England from 16-March-2020 to 26-April-2020. RESULTS: There were 640 COVID-19 cases (571/324,306 White, 31/4,485 Black, 21/5,732 Asian, 17/5,803 Other). Compared to the White study members and after adjusting for age and sex, Black individuals had over a 4-fold increased risk of being hospitalised (odds ratio; 95% confidence interval: =4.32; 3.00-6.23), and there was a doubling of risk in the Asian group (2.12; 1.37, 3.28) and the ‘other’ non-white group (1.84; 1.13, 2.99). After controlling for 15 confounding factors which included neighbourhood deprivation, education, number in household, smoking, markers of body size, inflammation, and glycated haemoglobin, these effect estimates were attenuated by 33% for Blacks, 52% for Asians and 43% for Other, but remained raised for Blacks (2.66; 1.82, 3.91), Asian (1.43; 0.91, 2.26) and other non-white groups (1.41; 0.87, 2.31). CONCLUSIONS AND RELEVANCE: Our findings show clear ethnic differences in risk of hospitalization for COVID-19 which do not appear to be fully explained by known explanatory factors. If replicated, our results have implications for health policy, including the targeting of prevention advice and vaccination coverage.